2011
DOI: 10.1039/c1an15525c
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of early stage nasopharyngeal carcinoma using ultraviolet autofluorescence excitation–emission matrix spectroscopy and parallel factor analysis

Abstract: We report the diagnostic ability of ultraviolet (UV)-excited autofluorescence (AF) excitation-emission matrix (EEM) spectroscopy associated with parallel factor (PARAFAC) analysis for differentiating cancer from normal nasopharyngeal tissue. A bifurcated fiber-optic probe coupled with an EEM system was used to acquire tissue AF EEMs using excitation wavelengths between 260 and 400 nm, and emission collection between 280 and 500 nm. A total of 152 AF EEM landscapes were acquired from 13 normal and 16 nasopharyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Studies have shown that each endogenous fluorophore possesses its own emission band and wavelength maximum 33 . In our experiment, the 400 nm-excited lifetime images were obtained in the 525-nm channel, which have deviated from the emission peaks of the endogenous fluorophores with a high sensitivity to NPC 17 33 ; such a deviation may have led to the absence of significant differences in AF lifetimes between normal (NP69 and MSC) and cancerous (CNE-2) cells 33 . The luminescence spectra (the colour curves) of CNE-2, NP69 and MSC cells after the uptake of Au/Gd@MCM-41 are also shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Studies have shown that each endogenous fluorophore possesses its own emission band and wavelength maximum 33 . In our experiment, the 400 nm-excited lifetime images were obtained in the 525-nm channel, which have deviated from the emission peaks of the endogenous fluorophores with a high sensitivity to NPC 17 33 ; such a deviation may have led to the absence of significant differences in AF lifetimes between normal (NP69 and MSC) and cancerous (CNE-2) cells 33 . The luminescence spectra (the colour curves) of CNE-2, NP69 and MSC cells after the uptake of Au/Gd@MCM-41 are also shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The detection of autofluorescence (AF) allows the investigation of the epithelial layer, as the vast majority of nasopharyngeal tumours initiate in the epithelial tissue layer 17 . Many key endogenous fluorophores are specific to normal and cancerous NP cells and produce a strong autofluorescence (AF) signal under ultraviolet (UV) excitation between 260 and 400 nm 17 . Figure 3(a,b) show the AF spectra (black curves) and the FLIM images of AF from NP69 and CNE-2 cells, respectively, at 525 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach could employ powerful algorithms, such as parallel factor analysis (PARAFAC) conducted for the first time on biological tissues to differentiate carcinoma from normal nasopharyngeal tissue. 35 Analogous to the confocal Barrett's classification, Table 1 serves as a foundation from which to build on. 25,26 As it has taken decades to correlate abstract images of stained tissue sections and establish traditional histology, a similar effort may be needed to establish the correlation of characteristic features observed in the images obtained using new technologies such as the UV AF microscopy method discussed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, autofluorescence arising from "interesting" endogenous molecules may also carry useful spectroscopic information. Autofluorescence spectra of, for example, NAD(P)H [53], flavins and flavoproteins [54], advanced glycation end-products (AGEs) [55], collagen and elastin [56], lipofuscins [57] and protoporphyrin IX [58] can provide insights into normal and pathological specimens [59,60].…”
Section: Validation (Or Identification)mentioning
confidence: 99%